Incidental Finding of Untreated Secondary Syphilis in a Pregnant Woman in a Limited Resource Area: A case report - Edelyne Chelsea; Hanny Nilasari; Yudo Irawan; Raymond Surya (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Syphilis is a global burden of sexually transmitted infection caused by Treponema pallidum sub. pallidum with high epidemiology worldwide, including Indonesia. Syphilis in pregnancy is the second-leading cause of stillbirth. Syphilis can cause perinatal consequences for a developing fetus if left untreated. Case: We found an incidental case of untreated secondary syphilis in a 21-year-old primigravida woman. She had multiple erythematous, hyperpigmented maculopapular rashes on her trunk and extremities, as well as condylomata lata on her vulva. The Treponema pallidum-rapid (TP-rapid) test was reactive. During her pregnancy, she never received antenatal care or any treatment for her condition. The patient underwent caesarean section. The baby showed no clinical sign of congenital syphilis but tested reactive for TP-rapid. In a single dose, both the patient and her baby received a benzathine-penicillin G intramuscular injection in single dose. The baby was referred back to primary health care for close monitoring of its growth and development. Discussion: This is a missed case of typical secondary syphilis. Due to the failure of early diagnosis, early treatment for the patient was not possible. The baby was also at high risk of congenital syphilis. In a limited resource area, primary healthcare facilities play a key role in solving the problem through updated data collection of pregnant women, comprehensive antenatal care, education about sexually transmitted infection, early screening, and treatment.